Micro-models of criminal careers: A synthesis of the criminal careers and life course approaches via semiparametric mixed poisson regression models, with empirical applications - Land, Kenneth C. (Journal of quantitative criminology, 1996)
Much recent research and debate in criminology have centered around how to conceptualize and model longitudinal sequences of delinquent and criminal acts committed by individuals. Two approaches dominate this controversy. One originates in the criminal careers paradigm , which emphasizes a potential heterogeneity of offending groups in the general population—thus leading to a distinction between incidence and prevalence of criminal offending, a focus on the onset, persistence, and desistence of criminal careers, and the possibility that criminals are a distinctive group with constant high rates of offending. Another approach places criminal events within a broader context of studies of the life course by explicitly substituting the conceptualization of “social events” for that of “criminal careers”. With respect to analytical models, this approach emphasizes a potential heterogeneity of offenders with respect to order of criminal events from first to second to higher orders and thus suggests an analysis of the “risks” or “hazards” of offending by order of offense. Some extant commentaries on the criminal careers and life course approaches to conceptualizing and modeling longitudinal sequences of delinquent and criminal events committed by individuals have emphasized their differences and incompatibilities. In contrast, we apply recently developed semiparametric mixed Poisson regression techniques to develop conditions under which the two conceptual/modeling approaches are formally equivalent. We also modify the semiparametric mixed Poisson regression model of criminal careers to incorporate information on order of the delinquent/criminal event and develop an empirical application. This modification demonstrates the complementarity of the criminal careers and life course approaches, even though they have somewhat different foci.